From revolution to reform and back: EU-Security sector reform in Ukraine. Issue 4 (2nd October 2018) - Jayasundara-Smits, Shyamika
ABSTRACT: Security Sector Reform (SSR) is an important element of the EU's external intervention toolkit. In an increasingly uncertain global security environment, the EU has currently stepped up its SSR endeavours. However, success of these efforts largely depends on the EU's capabilities in navigating complex context-specific challenges. In particular the EU needs to be able to simultaneously address the functional and normative-societal imperatives that underpin SSR. This article considers the case of the EU's ongoing SSR mission to Ukraine – the European Union Advisory Mission (EUAM). It asks, what are the unique context-specific challenges faced by EUAM in Ukraine? How do these challenges influence the EU's ability to satisfy both the normative-societal imperative of SSR through the EUAM? This article mainly relies on secondary data, and applies a "Whole of Society" approach to conflict prevention and peacebuilding (WOS). Amidst a situation of ongoing multiple armed conflicts and EU-Russian relations of mutual dependence, a key finding is that the mandate of the mission has become more narrow and exclusive by sacrificing vertical coherence and the normative-societal imperative. We recommend EUAM adopt a more "revolutionary" approach to SSR, by adhering to key SSR normative principles so that the mission can overcome the challenges of the unique reform environment of Ukriane. This will also make it able to contribute more meaningfully to the wider reform process in an effective and sustainable manner.